The T‐shaped FST pharyngoplasty step‐by‐step closure technique. Issue 12 (15th September 2022) - Petruzzi, Gerardo; Di Giorgio, Danilo; Leone, Federico; Pichi, Barbara; Campo, Flaminia; De Virgilio, Armando; Valentini, Valentino; Pellini, Raul
Abstract: Pharyngocutaneous fistula is one of the most common and serious complications associated with total laryngectomy. Numerous studies tried to evaluate causative and predisposing factors associated with this complication, but data are considerably variable and there is still no international consensus. Incidence rate varies considerably between studies, with reported rates from 3% to 65%. This 4K video presents our T‐shaped four‐step technique (FST) for closing the pharyngeal mucosa after total laryngectomy in a step‐by‐step manner. All sutures were performed by braided absorbable 3/0 26 mm 1/2c (Vicryl plus 3.0; Ethicon, Somerville, NJ, USA). Recordings were performed using a Karl Storz 4K 3D VITOM® exoscope (Karl Storz SE & Co. KG, Tuttlingen, Germany). We have been described this technique through a high‐definition video, showing each step, and tips from the authors. Our T‐shaped pharyngoplasty closure technique can be divided into four steps: 1. "Key Stitches"; 2. "Area Refinement Stitches"; 3. "Modified Connell Suture"; 4. "Modified Purse String Suture." Our T‐shaped FST closure technique proved to be an effective and reproducible method, which we feel could be the preferred choice for primary pharyngoplasty closure.